Romanticism and Time : Literary Temporalities. - Laniel-Musitelli, Sophie; Sabiron, Céline. (Cambridge, UK : Open Book Publishers, 2021)
'Eternity is in love with the productions of time'. This original edited volume takes William Blake's aphorism as a basis to explore how British Romantic literature creates its own sense of time. It considers Romantic poetry as embedded in and reflecting on the march of time, regarding it not merely as a reaction to the course of events between the late-eighteenth and mid-nineteenth centuries, but also as a form of creative engagement with history in the making.
Intro -- Contents -- Acknowledgements -- Introduction: The Times of Romanticism -- Section I -- Restoration, Revival, and Revolution across Romantic Europe -- 1. Future Restoration -- 2. Anthropocene Temporalities and British Romantic Poetry -- 3. Beethoven: Revolutionary Transformations -- Section II -- Romantic Conceptions of Time -- 4. The Temporality of the Soul: Immanent Conceptions of Time in Wordsworth and Byron -- 5. 'Footing slow across a silent plain': Time and Walking in Keatsian Poetics -- Section III -- The Poetics of Time -- 6. Contracting Time: John Clare's The Shepherd's Calendar -- 7. Book-Time in Charles Lamb and Washington Irving -- 8. 'A disciple of Albertus Magnus [...] in the eighteenth century': Anachronism and Anachrony in Frankenstein -- Section IV -- Persistence and Afterlives -- 9. Heaps of Time in Beckett and Shelley -- 10. 'Thy Wreck a Glory': Venice, Subjectivity, and Temporality in Byron and Shelley and the Post-Romantic Imagination -- Section V -- Romanticism and Periodisation -- Romanticism and Periodisation: A Roundtable -- List of Contributors -- List of Figures -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books